Employment recovery capital in the treatment of substance use disorders: Six-month follow-up observations. (1st December 2019) - Sahker, Ethan; Ali, Saba Rasheed; Arndt, Stephan
Highlights: Employment recovery capital predicts substance use treatment completion. Employment recovery capital predicts maintained/increased use at follow-up. Employment recovery capital change predicts abstinence at follow-up. Best predictors of abstinence include change in months employed and work missed. Interventions could focus on improvement of employment recovery capital. Abstract: Background: Recovery capital represents client strengths associated with substance use disorder (SUD) recovery. Employment is part of recovery capital supporting long-term recovery. However, specific employment recovery capital (ERC) factors associated with SUD recovery are not well understood. Methods: The present study used retrospective logistic regression modeling to predict treatment completion at discharge and substance use at six-month follow-up from employment variables at intake and follow-up. An additional exploratory follow-up of ERC Change is further investigated. Existing clinical data from a random selection of all Iowa SUD treatment facilities receiving public funding from 1999-2016. Clients in the study (N = 8, 925) were a mean age of 31.7 (SD = 11.8), mostly male (67.2%), and primarily White (86.6%). Measurements included substance use, treatment completion, ERC Change, demographic, and treatment statistical control variables. Results: Results demonstrated that employment variables at intake predicted greater successful treatment completion, p < 0.0001. However, the same employment variables were predictive of maintained and increased use at six-month follow-up. Further investigation showed the best predictors of post-treatment recovery was a change in employment variables including months employed increase (AOR = 1.53, 95% CI = 1.34–1.75) and days missed from work due to substance use decrease (AOR = 2.43, 95% CI = 2.00–2.96). Conclusions: Researchers and providers can help improve client recovery with intervention design, consultation, and policies focused on vocational growth in addition to employment benchmarks of gross income, full-time employment, occupation, primary support, months employed, and work missed. ERC is a promising route to improve the lives for those involved with substance use disorders.